Role of Remittance in Livelihood Development of Women: A Case of Jhumka Village, Sunsari - Tamang, Bal Bahadur (GS Spark: Journal of Applied Academic Discourse, 2024)
The arrival of remittances has an impact, on the economic progress of rural regions by specifically improving the lives of women residents in those areas. This research explores how remittances contribute to the advancement of women’s livelihood in Jhumka Village in Sunsari District, Nepal. The study analyzes remittances’ social and personal effects on women through group discussions and detailed interviews focusing on topics like household decision-making, women’s empowerment, and financial self-sufficiency. After examining research on remittances and the impact on gender-related economic growth in the Jhumka region and comparing it to the real-world data obtained through field studies, I agree with the fact that remittances play a crucial role in enhancing women’s quality of life in Jhumka by enabling them to invest in education and healthcare as well as start their businesses which subsequently lead to social changes that support gender equality efforts. Nonetheless, the study also highlights obstacles like dependence on income sources and uneven progress results that require investigation.